PENGARUH INTRAVENA DRESSING TRANSPARAN TERHADAP KEJADIAN FLEBITIS: TINJAUAN SISTEMATIS - Wicke Afriza; Abdilah Septiana Putri; Yeni Astuti; Suci Rahmadia (Nusantara Hasana Journal, 2024)
Phlebitis is a common complication of intravenous infusion. Several types of intravenous dressings have been reported to prevent phlebitis, but research results are still inconsistent. Objective: To systematically review the effect of using transparent dressings on the incidence of phlebitis in inpatients receiving intravenous therapy. Method: An article search was carried out in 3 databases, namely PubMed, Proquest and Google Scholar with the keywords "phlebitis", "transparent dressing","intravenous therapy". Inclusion criteria included Static Group Comparison, Cohort prospective , quasi-experimental research design, a sample of adult inpatients, and outcomes in the form of phlebitis incidence. Results: There were 335 articles, and after screening only 4 articles met the criteria for review. Conclusion: Transparent dressing effective in reducing the incidence of phlebitis in intravenous therapy for inpatients. There needs to be an SOP for choosing the type of intravenous dressing in the hospital to prevent phlebitis.